Does the Dividend Policy, Liquidity, Activity and Leverage Increases Corporate Value? (Evidence on the Jakarta Islamic Index) - Idil Rakhmat Susanto; Ismail Badollahi; Wahyuni Wahyuni; Nurhidayah Nurhidayah (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to examine the effect of dividend policy, liquidity, activity, and leverage on companies listed on the Jakarta Islamic Index. The sample used is a balanced data panel in 16 manufacturing companies from 2014 to 2018. This study uses multivariate analysis with a random effect model as a testing model for the research sample. The results show that dividend and liquidity policies are able to increase firm value, this shows that companies with good dividend policies and benefits for various parties can have a positive impact on increasing corporate value as well as good liquidity which will certainly be a positive signal for investors and have a good impact company. Activity and Leverage have no effect on Firm Value, this is also evidence that inefficient activities will have an impact on poor company productivity, and very high leverage can also be a negative signal for investors because the company will be seen only in debt to carry out its activities